The complete chloroplast genome and phylogenetic analysis of Salvia oxyphora Briq. 1896 (Nepetoideae, Lamiaceae). Issue 7 (3rd July 2022) - Pei, Yifei; Zhao, Guiping; Li, Xiwen; Yu, Dade; Cui, Ning
Abstract: Salvia oxyphora Briq. 1896 is a perennial herb in the family Lamiaceae native to Central Bolivia. In this study, the chloroplast genome of S. oxyphora was sequenced using the Illumina platform and was assembled for the first time. The complete plastid genome of S. oxyphora was 151, 014 bp in length including a large single-copy (LSC) region of 82, 293 bp, a small single-copy (SSC) region of 17, 531 bp, and a pair of inverted repeats (IR) regions of 25, 595 bp. The total GC content of this genome was 38.04%, and that of LSC, SSC and IR regions was 36.21%, 31.80% and 43.13%, respectively. A total of 114 unique genes of this genome have been annotated, including 80 protein-coding genes, 30 transfer RNA genes, and four ribosomal RNA genes. The maximum likelihood phylogenetic tree was constructed with 51 complete chloroplast genomes, illustrating the close relationship of S. oxyphora to the Brazil's native medicinal species S. splendens . The chloroplast genome of S. oxyphora provides a foundation for further studies on the adaptive evolution and genetic diversity of the genus Salvia .